Recommendations for the Effective Operation of MercedesBenz Bus Air Filters in Hot Climatic Conditions (Texas Journal of Engineering and Technology, 2022)
This article is devoted to the regeneration of air filters Mercedes-Benz buses, justified the number of optimal regeneration of clogged air filters. The dynamics of the aerodynamic resistance of air filters is experimentally and theoretically proved, and the second-order polynomials are obtained for the prediction of the change in their resistance by applying the methods of mathematical statistics.